PENGARUH MOTIVASI, KEMAMPUAN, PERSEPSI PERAN TERHADAP KEPUASAN PEGAWAI DI DINAS KEBUDAYAAN DAN PARIWISATA PROVINSI BENGKULU - Febzi Fiona (Management Insight: Jurnal Ilmiah Manajemen, 2018)
Abstract: The purpose of this research is to investigated the influence of ability and role perception to employee job satisfaction) at Dinas Kebudayaan dan Pariwisata Provinsi Bengkulu. This research use quantitative methods and qualitative methods. Data that used in this research is primary data of questionnaire. Population of the current research is 157 people. Distributing questionnaires to employees at Dinas Kebudayaan dan Pariwisata Provinsi Bengkulu taken as many as 113 people with proportionate stratified random sampling methodsAnalysis technique that used in this research is Regression Analysis from software SPSS 17. The result indicates that ability have a positive and significant effect to job satisfaction, role perception have a positive and significant effect to job satisfaction.Keywords : Ability, Role Perception, Job Satisfaction